"Stop eating lollies and do lots of sports": a prospective qualitative study of the development of children's awareness of dietary restraint and exercise to lose weight. Issue 1 (December 2015) - Rodgers, Rachel; Wertheim, Eleanor; Damiano, Stephanie; Gregg, Karen; Paxton, Susan
Abstract Background Beliefs surrounding the usefulness of dietary restriction and physical activity as means of body shape and size modification is already present in children as young as 5-years-old, and these beliefs may increase the risk of unhealthy weight control behaviours later in life. To date, however, little is known regarding the development of these beliefs in younger children. The aim of the present study was, therefore, to explore young (aged 3- to 5-years old) children's conceptualisations of dietary restriction and physical activity as means to change body size using a prospective approach. Methods A sample of 259 children (116 boys, 143 girls) participated in interviews at 3-, 4- and 5-years-old. Participants were shown silhouette figures of a child of their gender and age. Their responses to questions regarding how the figure could return to a previous thinner shape were qualitatively coded using thematic analysis. Results Children's responses revealed that while, for a subsample, modifications of food, eating, and exercise patterns were the most salient ideas, a number of other mechanisms of body change were also suggested. Responses also evidenced adoption or awareness of stigmatising attitudes towards overweight individuals (over 15 % by age 5). The proportion of children demonstrating an awareness of dietary restriction and physical exercise as methods for body size change increased significantly at each time point. While only 4.2 % demonstrated dieting awareness at 3-years-old, this proportion had risen to almost 28 % by 5-years-old (p < .001). Similarly, the proportion of children aware of exercise as a body change strategy rose from 2.3 to 16.3 % (p < .001), with 22 % of 5-year-olds mentioning general physical activity as a strategy. No gender differences were found. Conclusions Awareness of dietary restriction and physical exercise as strategies for weight loss and body change emerges as young as 3-years-old, and significantly increases from 3- to 5-years-old. Interventions aiming to promote healthy means of weight control and obesity prevention should consider that certain attitudes may already be present in very young children.